A importância do conhecimento em primeiros socorros na formação do professor de educação física - Ramos, Ana Maria da Conceição Pereira (Universidade Federal do Tocantins, 2022)
The present work addresses the importance of knowledge in first aid in the training of teachers in Physical Education, and aimed to identify the importance of knowledge in first aid during training in physical education. The specific objectives of this study were to describe the objectives of first aid at school; present the risks of accidents within the school; identify the importance of educators' knowledge about first aid and identify the importance of knowledge in first aid for physical education teachers. In this sense, the research was an integrative review, in a descriptive way, based on the scientific productions contained in the LILACS database and on the academic Google regarding first aid at school, in education and in physical education. Articles published between 2016 and 2021 were consulted, the search resulted in 186 articles and after entering the inclusion and exclusion criteria, 14 articles were analyzed. As a result, it was observed that the teachers had basic notions of first aid based on knowledge acquired in graduation, they highlighted that it is insufficient given the complexity of some urgent and emergency circumstances that may happen at school. It was noticed that the lack of security of teachers may be related to their training. Teachers report that the workload is insufficient, that the content of first aid is seen in a superficial way and with a lack of practices to assimilate and practice the content.